2019
DOI: 10.15728/bbr.2019.16.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Competencies and Strategic Behavior: a Study of Micro Entrepreneurs in an Emerging Country

Abstract: The purpose of this paper is to analyze the relationship between the entrepreneurial competencies and the strategic behavior patterns of entrepreneurs in response to the social and economic environment in which they operate, taking into consideration limitations that are common to emerging countries. The study takes a quantitative approach with a survey of 211 Individual Micro Entrepreneurs (IME) operating in the Brazilian state of Santa Catarina. The results demonstrated that there were differences between me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 23 publications
(41 reference statements)
1
19
0
1
Order By: Relevance
“…In the classification of Miles and Snow (1978), this first group fits in the prospector mode, because companies with these characteristics are precursors of innovation and for that, they need to identify new opportunities. The results are similar to those obtained by Gonçalves et al (2017) in MSEs in the Londrina (PR) city, and by Behling and Lenzi (2019) in the Santa Catarina state, where most of the companies analyzed fall into the prospector group. This is important, as the prospector type is considered to have the greatest growth potential (WEBER; GENESTE; CONNELL, 2015), in addition to being identified as the type with the highest profitability KEUNG, 2019).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…In the classification of Miles and Snow (1978), this first group fits in the prospector mode, because companies with these characteristics are precursors of innovation and for that, they need to identify new opportunities. The results are similar to those obtained by Gonçalves et al (2017) in MSEs in the Londrina (PR) city, and by Behling and Lenzi (2019) in the Santa Catarina state, where most of the companies analyzed fall into the prospector group. This is important, as the prospector type is considered to have the greatest growth potential (WEBER; GENESTE; CONNELL, 2015), in addition to being identified as the type with the highest profitability KEUNG, 2019).…”
Section: Resultssupporting
confidence: 84%
“…In the literature, studies were found on SMEs' SM, however, they are based on only one of the aspects addressed here or only mention the existence, nonexistence or importance of SM (BEHLING;LENZI, 2019;KEUNG, 2019;GONÇALVES et al, 2017;HABIB;HASAN, 2019;MORARU;POPA, 2018;SOARES;TEIXEIRA;PELISSARI, 2011;UPSON;GREEN, 2017;WEBER;GENESTE;CONNELL, 2015), this being a differential of this study. To meet the proposed objective, initially the theoretical aspects that underlie the SM analysis will be discussed and, later, a diagnosis will be made through cluster analysis.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a systematic review of the literature on incorporating entrepreneurial competences in higher education by Ferreras, Hernández-Lara, and Serradell-López (2017), the authors found that in the last decade, studies related to entrepreneurial competences and their relationship with the process teaching-learning has shown a considerable increase. Lenzi, Santos, Casado, and Kuniyoshi (2015), Behling and Lenzi (2019) argue that studies in the management area have sought to incorporate knowledge about the entrepreneurial profile combined with the context of competencies. The authors state that an entrepreneur can build and adapt his individualities to create an entrepreneurial competence, just as an individual can polish his capabilities.…”
Section: Entrepreneurial Competencesmentioning
confidence: 99%
“…communication skill), decision making competence to solve problems and competence of time management (Eravia et al, 2015). The competencies can be developed by training and accumulation of experience (Behling, 2017). Training activities include guiding, correcting, advising, mediating, advocating, facilitating, educating and supervising micro-businesses to grow into productive and competitive business.…”
mentioning
confidence: 99%